Material Basis of the Difference between Hedysari Radix and Honey-Processed Hedysari Radix in Buzhong Yiqi - Niu, Jiang-tao (Evid Based Complement Alternat Med, 2020)
OBJECTIVE: To compare the changes of chemical components of Hedysari Radix (HR) before and after honey-processing, and to explore the material basis of the difference between HR and honey-processed Hedysari Radix (HPHR) in Buzhong Yiqi. METHODS: Different compounds in aqueous extracts of HR and HPHR were analysed by UPLC-MS. A rat model of spleen qi deficiency was established. The rats were treated with different doses of water extracts of HR or HPHR, and pathological differences in spleen tissue, serum levels of D-xylose, gastrin (GAS) and amylase (AMS) interleukin-2 (IL)-2 and tumour necrosis factor-α (TNF-α), as well as spleen and thymus indices, were used as indicators. Differences in the efficacy of HR and HPHR in Buzhong Yiqi were studied. RESULTS: The research showed that compared with the blank group, the spleen tissue of rats in the model group showed spleen tissue damage, which mainly manifested as unclear boundaries between red pulp and white pulp, irregular spleen morphology and irregular arrangement, and the structure of white pulp destruction, less lymphocytes, the number of germinal centers decreased or atrophied. Compared with the model group, the middle and high dose groups of HR and HPHR had protective effects on spleen tissue of spleen-qi deficiency rats, and HPHR had a stronger effect; compared with those in the model group, rats in each treatment group showed remarkably higher serum D-xylose, GAS and AMS levels and thymus and spleen indices, and remarkably lower serum IL-2 and TNF-α levels, among which HPHR group showed better regulation effect than HR group. A total of 16 differential compounds were found in the aqueous extracts of HR and HPHR, of which 10 compounds in HPHR were up regulated, while 6 compounds were down regulated compare to HR. CONCLUSION: The results indicated that both HR and HPHR can improve spleen qi deficiency syndrome of rats, the pharmacodynamic effect of the latter was better than the former. Differences in components of HR and HPHR potentially leading to variations in efficacy.